1990
DOI: 10.1111/j.1439-0442.1990.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia Reduces Rate of Disappearance of Glucose from Plasma

Abstract: The influence of hypocalcemia on glucose disposal from plasma was studied in 4.5 to 24 kg weaned, fasted, calcitriol deficient piglets, which suffered from type I inherited pseudo vitamin D deficiency rickets. The plasma glucose concentration of the piglets was clamped to 40 Yo above its preinfusional level by a continuous intravenous infusion of glucose. This suppressed hepatic glucose production. Since the clamped plasma glucose concentration was below its renal threshold, the rate of steady state glucose in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…By this method, the glucose turnover will probably be underestimated, due to recycling of label in the course of the longer lasting experiment. In our own glucose clamp experiments carried out in piglets of the same strain and of the same age as those used here the estimated glucose turnover was two to three times higher (Schlumbohm & Harmeyer, 1990) than in this experiment. This demonstrates that the glucose turnover in growing pigs is subject to great variability and may quite markedly be influenced by the experimental conditions.…”
Section: Effect Of Hypocalcaemia On the Metabolism Of ª_bhbsupporting
confidence: 40%
See 2 more Smart Citations
“…By this method, the glucose turnover will probably be underestimated, due to recycling of label in the course of the longer lasting experiment. In our own glucose clamp experiments carried out in piglets of the same strain and of the same age as those used here the estimated glucose turnover was two to three times higher (Schlumbohm & Harmeyer, 1990) than in this experiment. This demonstrates that the glucose turnover in growing pigs is subject to great variability and may quite markedly be influenced by the experimental conditions.…”
Section: Effect Of Hypocalcaemia On the Metabolism Of ª_bhbsupporting
confidence: 40%
“…One reason for this increase is possibly an increased lipomobilization in hypocalcaemic piglets brought about by a reduced insulin-mediated depression of lipolysis. It has been reported that hypocalcaemia not only reduces insulin secretion (Pento et al 1974) but also increases insulin resistance of peripheral tissues (Schlumbohm & Harmeyer, 1990). Both effects may enhance lipomobilization.…”
Section: Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased risk of ketosis could not be attributed to differences in milk yield between normocalcemic and SCHC cows as milk production did not differ, thus the increased risk of ketosis observed herein and in other studies may be caused by mechanisms different than changes in milk production per se and are probably linked to alterations in glucose metabolism. For instance, Schlumbohm and Harmeyer (1990) reported that hypocalcemia induces a reduction of glucose utilization in pigs, which seems to be mediated by a decreased insulin secretion under low calcemia (Witzel and Littledike, 1973); however, whether this mechanism could be involved in ruminants is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Our own experiments with pigs (Schlumbohm & Harmeyer, 1990) and sheep ) have indicated that hypocalcaemia might be of significance in vivo for the control of glucose metabolism. A reduction of glucose turnover in the presence of hyperketonaemia has also been reported in humans (Baron et al 1989) and dogs (Shaw & Wolfe, 1984).…”
mentioning
confidence: 94%